Case analysis and clinical implications of interconnected accessory abductor pollicis longus tendons and abductor pollicis brevis muscles - Ethan L. Snow; Andrew C. White; Alexis M. Tyce; Travis L. McCumber (Elsevier, 2022)
Introduction: The pollex (i.e., thumb) is critical to hand function. Abduction, generated by the abductor pollicis longus (APL) and brevis (APB) muscles, and extension, primarily generated by the extensor pollicis longus (EPL) and brevis (EPB), are two major pollex movements. Uncharacteristic cleavage of APB during development can form an accessory APB (a-APB). In addition, APL, EPB, and EPL can develop accessory tendons (a-tendons) to the pollex. However, reports of these anomalies occurring simultaneously and interconnected are scarce. The objective of this study is to analyze a unique case of bilateral APL a-tendons which distally form the origins of a-APB muscles and discuss its clinical implications. Materials and methods: Left and right forearms and hands of one human cadaver with bilateral APL a-tendons forming the origins of a-APB muscles were dissected, and the attachment sites of the anomalies were noted. The left side anomalies were photographed in situ since they exhibited a cleaner dissection field. The left side interconnected APL, a-APB, and APB were collectively detached from the cadaver, splayed, and photographed. The tissues were returned to their in-situ positions, cross-sectioned with EPB in the first extensor compartment, and photographed. Fascicle bundle length, pennation angle, and mass were measured for each left and right APL, a-APB, and APB muscle belly to calculate the physiological cross-sectional area and maximal isometric force (Fmax) generating capacity of each muscle. Averages of left and right data were used to discuss the functional impacts of the non-typical morphologies and their respective clinical implications. Results: The typical APL tendon displayed normal distal attachment to the base of the first metacarpal. The APL a-tendon originated from the deep surface of the APL muscle belly and exhibited two distal attachments: its main portion (137.48 mm long, 2.44 mm wide) to the origin of a-APB and a short, distal bifurcation to the trapezium. The APL tendon had three distinct slips, and stenosis of the APL a-tendon in the first extensor compartment was visible. Mean Fmax for APL, a-APB, and APB were 63.24 N, 8.31 N, and 12.05 N, respectively. Conclusions: This study presents a rare case of interconnected APL and a-APB via APL a-tendon with bifurcation to trapezium. The cumulative Fmax of APL and a-APB may be limited by the short a-tendon attachment angle to trapezium, and forceful pull on the trapezium with concurrent pressure from the APL a-tendon's distal attachment may lead to subluxation and/or osteoarthritis of the thumb's carpometacarpal joint. As suggested by visible stenosis of the APL a-tendon, its presence in the first extensor compartment would likely crowd APL and EPB and cause de Quervain's tenosynovitis. Furthermore, the long, robust APL a-tendon may instigate intersection syndrome from wrapping over the extensor carpi radialis longus tendon, but the APL a-tendon may at least serve as a sufficient candidate for tendon transfer or graft surgeries. In these regards, this report may serve as a valuable resource for orthopedic surgeons, occupational and physical therapy providers, and medical educators when presented with a similar clinical or educational case.